PENGARUH PENGGUNAAN MEDIA SMART LITTLE BOARD TERHADAP KEMAMPUAN MENGENAL HURUF HIJAIYAH USIA 5-6 TAHUN DI PAUD AL IKHWAN SERI BANDUNG OGAN ILIR - Istiqomah, Galuh; Imtihana, Aida; Cindrya, Elsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The ability to recognize Arabic letters (Hijaiyah) is a fundamental skill that is crucial for early childhood as an initial stage in reading the Qur’an, as well as supporting their language and cognitive development. However, observations at PAUD Al Ikhwan Seri Bandung, Ogan Ilir, showed that the ability of children aged 5-6 years to recognize Hijaiyah letters is still relatively low. This condition is caused by the limited and less engaging learning media, which easily makes children feel bored. Based on this, the purpose of this study is to determine: (1) the initial ability of children to recognize Hijaiyah letters before using the Smart Little Board, (2) the children’s ability after the implementation of the Smart Little Board, and (3) the extent to which this media influences the improvement of Hijaiyah letter recognition in children aged 5-6 years at PAUD Al Ikhwan Seri Bandung, Ogan Ilir. This research used a quantitative approach with an experimental method and a one-group pretest-posttest design. The subjects of the study involved 15 children in group B1. Data were collected through tests and observations, then analyzed using validity and reliability tests, normality and homogeneity tests, as well as hypothesis testing using the Paired Samples T-Test. The results of the study showed an improvement in children’s ability to recognize Hijaiyah letters after using the Smart Little Board. The improvement was evident from the comparison between pretest and posttest scores. The hypothesis test showed a significance value (2-tailed) = 0.000, meaning 0.000 < 0.05, so H₀ was rejected and Hₐ accepted. This confirms that the use of the Smart Little Board has a significant effect on the ability of children aged 5-6 years at PAUD Al Ikhwan Seri Bandung, Ogan Ilir to recognize Hijaiyah letters.